Exploring Junior High School Students’ Needs for Developing Local Folklore-Based English Learning Materials - Maghfirah Sabtu; Karolis Anaktototy; Wenda Marlin Kakerissa (ITScience (Information Technology and Science), 2026)
This study aims to explore junior high school students’ needs for the development of local folklore-based English learning materials. The study employed a descriptive research design using a mixed-method approach, combining quantitative and qualitative data. The participants were 25 eighth-grade students from a junior high school in Ternate. Data were collected through a questionnaire consisting of both closed-ended and open-ended questions. The quantitative data were analyzed using descriptive statistics, while the qualitative data were analyzed through thematic analysis. The findings revealed that students experienced difficulties in several English skills, particularly speaking, as well as challenges related to vocabulary and grammar. In addition, most students had limited experience in learning English through local folklore, although they were somewhat familiar with such stories. Despite this, students demonstrated positive attitudes toward folklore-based learning and expressed interest in using stories from their own cultural background. They also showed a preference for interactive learning activities such as storytelling, role-play, and group discussions. These findings indicate that local folklore has strong potential to support the development of meaningful and culturally relevant English learning materials. Such materials can enhance students’ language development, motivation, and engagement. Therefore, incorporating students’ needs into the development of folklore-based English learning materials is essential to ensure their effectiveness and relevance in the learning process.